INVESTIGATION OF THE EFFECT OF HEAT TREATMENT ON RESIDUAL DEFORMATION CHIPPER KNIVES - A. V. Alifanov; V. N. Alekhnovitch; A. М. Milyukova; V. V. Tsuran (Литьë и металлургия)
To carry out experimental studies of the influence of temperature modes on residual deformation of the sample-ing knives were manufactured pilot models of chipper knives 6HV2S steels (basic) and U8A 9HF each in size up to its analog (finished knife). We draw on the modes recommended for these steels.The experimentalresultsshowed that the samples with smallsize and relatively large thickness after THEN do not have any permanent deformations. Samples ments concerning thin and having a rectangularshape (length 300 mm), then there are residual after deformation as Trough. The magnitude of the deflection is greater the smaller the ratio of the thickness of the sample to its length and width. It is found that the samples made from steel 6HV2S have a deflection value smaller than the samples of steel grades and 9HF U8A.Repair any defects in the form of troughs manage curved by heating the samples to the tempering temperature and the subsequent exposure between steel plates in a hydraulic press under a load to cool the workpiece.Thus, as a result of the research found that the residual deformation-tion (trough) samples of knives from different grades (6HV2S, 9HF, U8A) has a different value, depending on the geometrical parameters of knives (length, thickness, width) and grades. The deflection can be easily eliminated by additional straightening.In the course of the work of steel 6HV2S supplied to the Belarusian market of Russia, at the branch of JSC «Atlant» -BSZ it was manufactured a few sets of prototypes chipper knives, intended for testing in a production environment on the woodworking enterprises of the republic (of «Ivatsevichidrev», JSC «Vitebskdrev/»).Production tests of experimental knives made in accordance with the process technology-mi, developed in Barga, showed their compliance with production requirements and also require-ments of state standards, which allows recommend them for a wide introduction to woodworking factories, specializing in the production of wood chips.